Vivências curriculares na licenciatura em matemática no CESP/UEA/Parintins - Silva, Paulo Sérgio Ribeiro da (2013)
His work demonstrates the type of treatment given to each curricular theory throughout the history of mathematics teaching in CESP in the period between the years 2001-2012, and teaching in PPP's Degree in Mathematics in CESP/UEA/PARINTINS. What are the placements of students with their formative experiences and experiences obtained in the process of teaching mathematics course, considering situations, models and experiences, enabling the understanding of curriculum theories in their practical conduct in making teaching in the classroom, providing future teachers further insight into what is be a math teacher. For that important steps were followed. Initially it was observed teaching practice of educators in the university so that they could be answered questions about his classes, pedagogical practices used, and the challenges that math teachers have with respect to the act of teaching. These processes were checked students' ideas and teachers in the process of teaching and learning about the topic at hand, so that the results could be observed in this process. It is hoped that this research will contribute in order to interact with the teaching of mathematics in order to make their classes, enriched with pedagogical practices coming trends in education, making their classes more efficient.